Abrasive Technology Characteristics and Applications - Rudawska, Anna (IntechOpen, 2018)
The subject matter of this book is the information on the abrasive technology methods, the characteristics of the methods (for example, the technological parameters, tools, and machines), innovative methods, characteristics of surface structure and surface properties after this type of mechanical process, and application in various industrial branches and other technical and technological domains. Abrasive technology is very important, for example, in precision component manufacturing and nano-technology devices. The aim of this book is to present information on the characteristics and applications of abrasive technology, abrasive tools, tests, and also the innovative methods of this technology. This information enables scientists, engineers, and designers to ensure the soundness and integrity of the fabricated components and to develop new techniques effectively.